LEARNING MODULE ANALYSIS OF PYTHAGOREAN THEOREM BASED ON SCIENTIFIC APPROACH - Cholily, Yus Mochamad; Kusgiarohmah, Putri Ayu (Jurnal Pendidikan Matematika dan IPA, 2022)
One of the basic competencies in class VIII contains the Pythagorean theorem. Surveys on students who have studied it, they still remember that the proposition is related to a right triangle. Interviews with students who understand the theorem show that they have a formulation of the relationship between the length of the hypotenuse and the side of the right angle. In detail they do not understand why this relationship can occur. That's because they memorized the formula instead of understanding it. For this reason, using the ADDIE development model, through this research a Scientific Learning-Based learning module was developed. This module was developed with the aim of helping self-study students to find their understanding of the Pythagorean theorem. Before being distributed, this module is analyzed to determine the validity and practicality of the module. The results of the study indicate that the module is valid, in accordance with the material, language and also there are scientific learning steps. Then, this module is said to be practical because through observation and interviews, the propositional module has met the criteria for practice assessment including, self-instructional, self-contained, stand-alone, adaptive, and user friendly.